Transapical Minimally Invasive Aortic Valve Implantation and Conventional Aortic Valve Replacement in Octogenarians - Strauch, Justus T.; Scherner, Maximilian; Haldenwang, Peter L.; Madershahian, Navid; Pfister, Roman; kuhn, Elmar W.; Liakopoulos, Oliver J.; Wippermann, Jens; Wahlers, Thorsten (The Thoracic and Cardiovascular Surgeon, 2012)
Objective Transcatheter aortic valve implantation (TAVI) has been developed to minimize the operative trauma in high-risk patients. Patient selection for TAVI is still subject to debate and octogenarians are often regarded as high-risk patients.Methods In this single-center study, data of 169 octogenarians who received conventional AVR (90) or TAVI (79) have been analyzed retrospectively according to the endpoint definitions of the Valve Academic Research Consortium to answer the following questions: (a) Should patients due to their age of 80 years or older be considered as high risk? (b) Is the EuroSCORE a suitable tool for estimating mortality after AVR or TAVI in octogenarians? (c) Is TAVI the procedure of choice for octogenarians?Results TAVI patients showed higher comorbid conditions concerning an existing renal dysfunction (31 vs. 56%, p = 0.001), peripheral vascular disease (6 vs. 30%, p < 0.001), diabetes (19% vs. 49%, p < 0.001), a decreased ejection fraction (LVEF < 30%: 2 vs. 13%, p < 0.05), and pulmonary hypertension (23 vs. 48%; p < 0.005) with an increase of the perioperative risk represented by logistic EuroSCORE (AVR 11% ± 1.27 vs. TAVI 38% ± 1.35; p < 0.0005) and STS Score (7% ± 0.52 vs. 14% ± 0.56; p < 0.0005). All-cause and cardiovascular-cause in-hospital or 30-day mortality was 5.6% (n = 5) and 3.4% (n = 3) in the AVR cohort and 8.8% (n = 7) and 7.6% (n = 6) in TAVI-patients (p = 0.55; p = 0.31), respectively. The overall combined safety endpoint at 30 days was 22.2% (n = 20) in AVR patients and 29.1% (n = 23) with regard to the TAVI group (p = 38). Analysis of cerebrovascular complications, vascular complications, and pacemaker revealed no significant differences. In the AVR group, actuarial survival at 6 months and 1 and 2 years was 89, 78, and 74%, respectively. Data of the TAVI patients are only available for a follow-up of 6 months and revealed a survival of 85%.Conclusion AVR and TAVI in octogenarians show comparable results, but the analyzed cohorts differ significantly in their risk profile. The results indicate an overrated perioperative mortality using the EuroSCORE but on the other hand logistic EuroSCORE represents articulately the different risk profile of the two groups. For this reason, we consider the EuroSCORE still to be a useful tool for preoperative risk assessment. Moreover, octogenarians cannot per se be considered as “true high risk” patients. Differentiated clinical judgment is most important for reasonable decision making.
Keywords: TAVI; aortic valve replacement; octogenarians; outcomes